1998
DOI: 10.1177/03635465980260021301
|View full text |Cite
|
Sign up to set email alerts
|

Concussion Incidence in Elite College Soccer Players

Abstract: A unique aspect of soccer is the use of the head for directing the ball. The potential for resultant head injuries has been the focus of discussions worldwide. Prior work has attributed neuropsychologic deficits to the cumulative effects of heading, without evaluating concussion rates in soccer players. We prospectively studied the seven men's and eight women's varsity soccer teams in the Atlantic Coast Conference during two seasons to document concussion incidence. The 29 concussions diagnosed over the 2 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
139
3
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(149 citation statements)
references
References 13 publications
5
139
3
2
Order By: Relevance
“…Concussions have been reported [18][19][20][21] to constitute 2% to 11% of all soccer injuries. Research by Barnes et al 18 indicated that male and female soccer players are at a 50% and 22% risk, respectively, of sustaining a concussion within a 10-year period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concussions have been reported [18][19][20][21] to constitute 2% to 11% of all soccer injuries. Research by Barnes et al 18 indicated that male and female soccer players are at a 50% and 22% risk, respectively, of sustaining a concussion within a 10-year period.…”
Section: Discussionmentioning
confidence: 99%
“…Research by Barnes et al 18 indicated that male and female soccer players are at a 50% and 22% risk, respectively, of sustaining a concussion within a 10-year period. Additionally, Boden et al 19 indicated that 17 (59%) collegiate men and 12 (41%) collegiate women were diagnosed with concussions over 2 soccer seasons. Although concussion rates for basketball players are slightly lower than those for football and ice hockey players, concussions in basketball players still accounted for 4.7% and 3.2% of all injuries for collegiate females and males, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…29 The most frequent cause of concussion in elite college soccer players was found to be contact with another player's head, elbow, or foot (47%), and contact with the ball (24%), ground/goalpost (17%), and combinations of objects (10%) were less frequent causes of concussions. 30 General sport-related concussion management and return-to-play guidelines have been published 31,32 ; however, there are currently no postconcussion return-to-play guidelines specific to soccer.…”
Section: Concussionmentioning
confidence: 99%
“…These investigations follow established findings on sex differences for verbal memory, perceptual motor speed, accuracy, and visuospatial tasks in the general neurocognitive literature. 4, 26 Covassin et al 10 reported that after concussion, female collegiate athletes demonstrated significantly poorer visual memory performance than male athletes. Similarly, Broshek and colleagues 5 reported that concussed female athletes were 1.7 times more likely to be cognitively impaired than male athletes.…”
mentioning
confidence: 99%